If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 1 = 7 + -1a Reorder the terms: 1 + 5a = 7 + -1a Solving 1 + 5a = 7 + -1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. 1 + 5a + a = 7 + -1a + a Combine like terms: 5a + a = 6a 1 + 6a = 7 + -1a + a Combine like terms: -1a + a = 0 1 + 6a = 7 + 0 1 + 6a = 7 Add '-1' to each side of the equation. 1 + -1 + 6a = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 6a = 7 + -1 6a = 7 + -1 Combine like terms: 7 + -1 = 6 6a = 6 Divide each side by '6'. a = 1 Simplifying a = 1
| 5q+7=3(4-p) | | 2(x-5)-3=4x-2(5+x) | | 7x-6=6x+1 | | 3x+13=5x-27 | | z^3=13j | | -22+21=m-10 | | H=9x+4c-9+3x-8c+3 | | 9C=72WHATISC | | M=-8x+2z-6+3x-4z+3 | | 23(9+x)=-5(4-x) | | 6+2(16-1*6)= | | SolveT=M(3+FG)forG | | D=-2y+9x-9+4y-9x+6 | | x^2-7x+90=0 | | 1(2x-1)/33 | | (x^2+4)(x^2-1)=0 | | 3-2x=5-4x | | ln^2(x)=4x | | B=-3x+9y-5y+5x-4x+6y | | 12=4x+6 | | L=-9c+4b-8b+6c-3c+6b | | 9y-5=0 | | 10+2(2x-1)=16 | | (ln^2x)=4x | | (lnx^2)=4x | | 2x^2-60x=2x^2 | | W=-5c+3c-9+4 | | z+3(2-i)=5+i | | S=-5b-3b+6-7 | | x^2+x+2.5=0 | | D=-9c+6c-8c | | 64/x=4 |